Visegrad Group and its Presence in the Mashriq Region - Döring Franziska (Sciendo, 2019)
This paper provides an outline about Hungary’s, Poland’s, Slovakia’s and Czechia’s relationships to the Mashriq region, especially Jordan, Israel and Egypt. The Central and Eastern European countries are considered both individually and collectively in the Visegrád group (V4). Therefore quantitative and qualitative indicators are examined. As one result it was found that in most cases the V4 had no common interests and consequently did not formulate common positions. But finally, the results of this work suggest that the migration crisis has indeed increased the interest of the Visegrád countries in the Mashriq and has accelerated their involvement to some extent both in the Mashriq region and within the European Union.